A fuzzy multi-objective linear programming model for solving remanufacturing planning problems with multiple products and joint components. (August 2017) - Su, Tai-Sheng
Highlights: This work demonstrates a novel FMOLP model in recyclable remanufacturing systems. The proposed model solves remanufacturing planning problems with multiple products. The proposed model evaluates cost-effectiveness, lead time and CO2 emissions. Abstract: Remanufacturing planning issues involve extremely complex strategic decisions within the supply chain system, especially considering the multiple products and joint components that are involved. It is very important to know how to determine the appropriate amounts of procurement quantity and lot size. In actual lot-sizing production-to-order problems for recoverable remanufacturing systems, input data or parameters are often imprecise or fuzzy. This work develops a fuzzy multi-objective linear programming (FMOLP) model that simultaneously minimizes total costs, lead time and CO2 emissions with reference to multiple products and joint components. The proposed model evaluates cost-effectiveness, lead time and CO2 emissions, while integrating multi-products, multi-suppliers, multi-components, joint components and multi-machines into one remanufacturing production system. The analytical results presented in this work are able to assist decision-making managers to better understand systematic analyses, and the potential for cost-effectiveness, lead time and CO2 emissions in recoverable remanufacturing planning.